2017
DOI: 10.1021/acsami.6b13306
|View full text |Cite
|
Sign up to set email alerts
|

Solid Electrolyte Interphase (SEI) at TiO2 Electrodes in Li-Ion Batteries: Defining Apparent and Effective SEI Based on Evidence from X-ray Photoemission Spectroscopy and Scanning Electrochemical Microscopy

Abstract: The high (de)lithiation potential of TiO (ca. 1.7 V vs Li/Li in 1 M Li) decreases the voltage and, thus, the energy density of a corresponding Li-ion battery. On the other hand, it offers several advantages such as the (de)lithiation potential far from lithium deposition or absence of a solid electrolyte interphase (SEI). The latter is currently under controversial debate as several studies reported the presence of a SEI when operating TiO electrodes at potentials above 1.0 V vs Li/Li. We investigate the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 43 publications
2
50
0
3
Order By: Relevance
“…Ferrocene was chosen as the free-diffusion redox mediator and the corresponding cyclic voltammetry between 2.8 and 3.8 V is shown in Figure 1A. The redox potential of the ferrocene/ferrocenium (Fc/Fc + ) combination is 3.26 V vs. Li + /Li, which is suitable for solid electrolyte interface characterization in LIBs (Zampardi et al, 2013;Ventosa et al, 2017). During the feedback measurement ( Figure 1B), the microprobe has an applied potential of 3.6 V vs. Li + /Li as it moves toward the substrate, and the current at the microprobe increases when the substrate is conductive due to the increase of Fc regeneration rate (positive feedback).…”
Section: Resultsmentioning
confidence: 99%
“…Ferrocene was chosen as the free-diffusion redox mediator and the corresponding cyclic voltammetry between 2.8 and 3.8 V is shown in Figure 1A. The redox potential of the ferrocene/ferrocenium (Fc/Fc + ) combination is 3.26 V vs. Li + /Li, which is suitable for solid electrolyte interface characterization in LIBs (Zampardi et al, 2013;Ventosa et al, 2017). During the feedback measurement ( Figure 1B), the microprobe has an applied potential of 3.6 V vs. Li + /Li as it moves toward the substrate, and the current at the microprobe increases when the substrate is conductive due to the increase of Fc regeneration rate (positive feedback).…”
Section: Resultsmentioning
confidence: 99%
“…Harutyunyana et al showed that high concentration of defects and edges in the electrode matrix is responsible for excess capacity in first few cycles [62]. Similarly, Schuhmann et al demonstrated that SEI formed in case of TiO 2 has high Liion transport ability and thereby it enhances the cycle stability of TiO 2 [39].…”
Section: Electrochemical Performancementioning
confidence: 99%
“…3 Raman spectrum of the B-TiO 2 Fig. 4 SEM images (a, b) and EDAX (c) of the B-TiO 2 NPs to 0.7-0.8 V vs Li [37][38][39]. The couple of peaks at 0.65 and 1.67 V in the cathodic sweep are assigned to insertion of lithium into TiO 2 matrix and to the structure transformation from tetragonal TiO 2 to orthorhombic Li x TiO 2 , where x is insertion coefficient.…”
Section: Electrochemical Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Based on these advantages, microelectrodes have been recently applied in the biomedical and analytical fields. Microelectrodes enable micromanipulation in the biomedical field and functionalization and characterization of solid surfaces in the analytical field when used in scanning electrochemical microscopy. Microelectrodes are fabricated in various forms, such as disk‐cylinders , spheres , and line‐arrays .…”
Section: Introductionmentioning
confidence: 66%